Pola Komunikasi dalam Program Qur’anic Leaderpreneur di Sekolah Rabbani Kota Bandung - Shanya Nadhira Adryna Putri; Ike Junita Triwardhani (Bandung Conference Series: Public Relations, 2024)
Abstract. It needs to be realized that the role of communication is very necessary in the life process for socialization, even in the learning process. Rabbani School is a school whose teaching and learning activities apply a typical curriculum, namely Quranic Leaderpreneur. Quranic leaderpreneur is the flagship program of the Rabbani school which was pioneered by the owner of Rabbani who wanted today's children to get out of their usual zone. The aims of this research are: 1). To analyze teachers to grow students' self-confidence, 2).Creating student creativity, 3). Implementation of the Qur'anic Leaderpreneur program at Rabbani School, Bandung City. In carrying out this research, researchers used a constructivism paradigm with a qualitative research approach and the method used was a case studyThe results of this research show that teachers have an important role in increasing students' self-confidence by providing support, praise and challenges according to their abilities. Teachers also facilitate students to explore creative ideas, enabling students to create innovative work. The Qur'anic Leaderpreneur concept combines Islamic values with entrepreneurial and leadership skills to meet the demands of education and character formation in today's Muslim society. Abstrak. Perlu disadari bahwa peranan komunikasi sangat dibutuhkan dalam proses kehidupan untuk melakukan sosialisasi, bahkan dalam proses pembelajaran. Sekolah Rabbani menjadi sekolah yang kegiatan belajar mengajarnya menerapkan kurikulum khas yaitu Quranic Leaderpreneur. Quranic Leaderpreneur adalah program unggulan sekolah Rabbani yang dipelopori oleh owner Rabbani yang ingin anak-anal zaman sekarang keluar dari zona biasanya. Tujuan dari penelitian ini yaitu : 1). Untuk menganalisis guru menumbuhkan rasa percaya diri siswa, 2). Menciptakan kreativitas siswa, 3). Penerapan program Qur’anic Leaderpreneur Sekolah Rabbani Kota Bandung. Hasil penelitian ini menunjukan bahwa guru memiliki peran penting dalam meningkatkan rasa percaya diri siswa dengan memberikan dukungan, pujian, dan tantangan yang sesuai dengan kemampuan mereka. Guru juga memfasilitasi siswa untuk mengeksplorasi ide-ide kreativitas, memungkinkan siswa menciptakan karya inovatif. Konsep Qur'anic Leaderpreneur menggabungkan nilai-nilai Islam dengan keterampilan kewirausahaan dan kepemimpinan untuk memenuhi tuntutan pendidikan dan pembentukan karakter dalam masyarakat muslim saat ini.